Profitability of the production of common bean (Phaseolus vulgaris L.), corn (Zea mays L.) and chili (Capsicum annuum.) in the municipality of Morelos, Zacatecas - Carrillo Martínez, Cristina Jared; Álvarez Fuentes, Gregorio; Aguilar Benítez, Gisela; García López, Juan Carlos; Contreras Servín, Carlos (Acta Universitaria, 2019)
The objective of the present work was to characterize the agricultural production systems of the municipality Morelos, Zacatecas and to calculate the profitability of its three main crops (beans, maize, and chili) under a conventional system during the agricultural year 2013. A simple random sampling was carried out with 26 farmers producing all three crops during the same agricultural cycle. The producers were typified, and the production costs per hectare, the profitability percentage, and the benefit-cost ratio (B/C) were estimated. The results show that the three crops are profitable. The cultivation of chili is the one that requires a greater investment, but it is the one that generates greater yields. It was also observed that the experience of producers, the incorporation of new technologies, and some practices of soil conservation are factors that allow a high level of productivity of the municipality.